Advances in Intelligent and Distributed Computing Proceedings of the 1st International Symposium on Intelligent and Distributed Computing IDC 2007, Craiova, Romania, October 2007 - Badica, Costin; Paprzycki, Marcin (Studies in Computational Intelligence, 2008)
This book presents the proceedings of the 1st International Symposium on Intelligent and Distributed Computing - IDC'2007, held in Craiova, Romania, October 2007. IDC 2007 was the first International Symposium bringing together researchers involved in intelligent and distributed computing to allow cross-fertilization and search for synergies of ideas and to enable advancement of research in these exciting sub-fields of computer science. The 34 contributions in this book cover a broad area of topics related to intelligent and distributed computing, systems and applications, including: autonomous and adaptive computing; constraint satisfaction; cooperation and coordination; data mining and knowledge discovery; distributed problem solving and decision making; e-business, e-health and e-learning; genetic algorithms; image processing; information retrieval; or intelligence in mobile and ubiquitous computing.